Taxonomic Revision of Tynanthus (Bignonieae, Bignoniaceae) - Medeiros, Maria Cláudia Melo Pacheco De; Lohmann, Lúcia Garcez (Phytotaxa, 2015)
Tynanthus is a genus of Neotropical lianas that are distributed from southern Mexico to southern Brazil. Extensive herbarium work, field studies and new molecular phylogenetic data were used as the basis to recognize 14 species in the genus. Here, we provide a detailed treatment of the group, including an identification key to all species recognized, as well as morphological descriptions, a complete list of synonymy, nomenclatural information, taxonomic notes, phenological data, information on habitat and distribution, and illustrations. Two species are circumscribed differently from earlier classifications, in particular Tynanthus elegans is synonymized with Tynanthus cognatus, while Tynanthus villosus is synonymized with Tynanthus polyanthus. In addition, Tynanthus goudotianus is treated as a doubtful name, and two recently described species are recognized, Tynanthus densiflorus and Tynanthus espiritosantensis. One species name is neotypified, Tynanthus caryophylleus, and nine species names are lectotypified, namely Cuspidaria ovalis, Tynanthus cognatus, Tynanthus elegans, Tynanthus guatemalensis, Tynanthus lindmanii, Tynanthus myrianthus, Tynanthus panurensis, Schizopsis chimonantha, and Schizopsis regnelliana. A complete list of doubtful and excluded names is presented.